A different look at the spin state of Co3+ ions in CoO5 pyramidal coordination - Hu, Zhimin; Haverkort, Maurits W. (Arxiv, 2003)
Using soft-x-ray absorption spectroscopy at the Co-$L_{2,3}$ and O-$K$ edges, we demonstrate that the Co$^{3+}$ ions with the CoO$_{5}$ pyramidal coordination in the layered Sr$_2$CoO$_3$Cl compound are unambiguously in the high spin state. Our result questions the reliability of the spin state assignments made so far for the recently synthesized layered cobalt perovskites, and calls for a re-examination of the modeling for the complex and fascinating properties of these new materials.